The service volunteer – loyalty chain: an exploratory study of charitable not‐for‐profit service organizations - Wisner, Priscilla S.; Stringfellow, Anne; Youngdahl, William E.; Parker, Lenore (Journal of Operations Management, 2005)
AbstractMany not‐for‐profit organizations rely on volunteers to help accomplish their service objectives. Although volunteers work alongside or in some cases replace employees in the delivery of service, incorporating volunteer labor into the service delivery system of the not‐for‐profit poses unique challenges. Understanding these challenges represents an important foundation‐building step in understanding the implications for service design and service operations when using volunteers. This paper identifies and describes service design and operational factors relevant to volunteer satisfaction in not‐for‐profit organizations. Using data collected from 288 volunteers working in 43 not‐for‐profit agencies, the study explores the elements of service delivery that impact volunteer satisfaction, and further tests the relationship between volunteer satisfaction and loyalty to the not‐for‐profit organization. Findings include that satisfied volunteers are more likely to remain for longer periods of time with the same organization, are more likely to donate financially to the not‐for‐profit, and are more likely to recommend the volunteer experience to others. Each of these outcomes helps to ensure the continued sustainability of the not‐for‐profit organization.